Spalax™ new generation: A sensitive and selective noble gas system for nuclear explosion monitoring. (September 2015) - Le Petit, G.; Cagniant, A.; Gross, P.; Douysset, G.; Topin, S.; Fontaine, J.P.; Taffary, T.; Moulin, C.
Abstract: In the context of the verification regime of the Comprehensive nuclear Test ban Treaty (CTBT), CEA is developing a new generation (NG) of SPALAX™ system for atmospheric radioxenon monitoring. These systems are able to extract more than 6 cm 3 of pure xenon from air samples each 12 h and to measure the four relevant xenon radioactive isotopes using a high resolution detection system operating in electron–photon coincidence mode. This paper presents the performances of the SPALAX™ NG prototype in operation at Bruyères-le-Châtel CEA centre, integrating the most recent CEA developments. It especially focuses on an innovative detection system made up of a gas cell equipped with two face-to-face silicon detectors associated to one or two germanium detectors. Minimum Detectable activity Concentrations (MDCs) of environmental samples were calculated to be approximately 0.1 mBq/m 3 for the isotopes 131m Xe, 133m Xe, 133 Xe and 0.4 mBq/m 3 for 135 Xe (single germanium configuration). The detection system might be used to simultaneously measure particulate and noble gas samples from the CTBT International Monitoring System (IMS). That possibility could lead to new capacities for particulate measurements by allowing electron–photon coincidence detection of certain fission products. Highlights: CEA developed a new noble gas station (SPALAX™ NG) for Comprehensive Test Ban Treaty purposes. SPALAX™ NG is able to extract more than 6 cm 3 of pure xenon in 70 m 3 air sampled during 12 h. Atmospheric radioxenon are measured using HPGe/Si electron-photon coincidences. SPALAX™ NG Minimum Detectable activity Concentrations are about 0.1 mBq/m 3 for 133, 133m and 131m Xe and 0.4 mBq/m 3 for 135 Xe.